History, Violence and Poetics: Saint-John Perse and René Char - Nathan Bracher (Studies in 20th & 21st Century Literature, 1991)
This essay explores the parallel yet opposite stances taken both personally and textually by Perse and Char with respect to drama of World War II. While Perse remained disdainfully aloof from public affairs after the defeat and proclaimed in his poetry his solidarity with all humanity, Char explicitly linked his writing to events, yet sought to create a human space removed from history's upheavals. Striving to transcend the vicissitudes of individual existence, Perse celebrates an epic vision of history that overlooks and even condones its violence. Focusing on the inconsistent, fragmentary nature of existence, Char prevents us from having any teleological delusions concerning war.
Keywords: Perse; Char; History; Violence; Poetics; drama; World War II; poetry; human space; space; existence; vision of history; violence; war; René Char; Saint-John Perse